Towel week suggestions in the season's latest offerings! ([Australia : s.n., 1940)
A colour screenprinted department store poster advertising "towel week". Depicts a woman holding an orange striped towel, with other colourful towels hung behind her. Set on a tan and green background.
Caption title.
Linen backed poster.
Original print size 54.5 x 34 cm.
Also available online
Keywords: Bath towels -- Advertising -- Posters; Advertising -- Retail trade -- Australia -- Posters; Sales promotion -- Australia -- Posters; Retail trade -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian